Non-linear association between C-reactive protein levels and length of stay in pediatric appendicitis patients undergoing laparoscopic appendectomy - Liu, Ming; Yang, Ping; Gou, Yunpeng (Frontiers in Pediatrics, 2024)
ObjectiveTo examine the correlation between C-reactive protein (CRP) levels at hospital admission and the length of stay (LOS) in pediatric patients with appendicitis who underwent laparoscopic appendectomy.MethodsWe retrospectively collected the clinical data from pediatric patients diagnosed with acute appendicitis and treated with laparoscopic appendectomy. Multivariate generalized linear regression analyses were performed to determine the independent relationship between CRP and LOS. Smooth curve fitting was constructed to examine the potential non-linear relationship between CRP and LOS. A segmented regression model was used to calculate threshold effects and determine the inflection point.ResultsA total of 815 participants were included in the study. Multiple linear regression analysis indicated that the higher the CRP levels, the longer the LOS. Fully adjusted smooth curve fitting suggested a non-linear relationship between CRP and LOS. A segmented regression showed that the inflection point value of CRP was 34.13 mg/L. A 1 mg/L increase in CRP levels was significantly associated with a 0.013-day increase in length of stay (95% CI: 0.009, 0.018; P < 0.001) when CRP levels > 34.13 mg/L. However, there was no significant association between CRP and LOS when CRP levels < 34.13 mg/L (P > 0.05).ConclusionThere was a non-linear association and threshold effect between CRP levels and LOS. CRP levels above 34.13 mg/L were associated with longer LOS in pediatric appendicitis patients. These findings contribute to the understanding of inflammatory markers in recovery dynamics and underscore the necessity for further research to investigate their potential clinical implications.